Effect of synergistic antioxidant against salinomycin toxicity in broiler chicken - Kamashi, K; Reedy, A Gopala; Reddy, K S; Reddy, V R (The Indian Journal of Animal Sciences, 2005)
Salinomycin toxicity was evaluated at therapeutic (6O ppm) and toxic (120 ppm) dose levels and the efficacy of a synergistic antioxidant (SA) was assessed for prophylactic and therapeutic management of salinomycin toxicity in broiler chicks. Day-old male broiler chicks were randomly divided into 7 groups consisting of 6 chicks each. Groups 1, 2 and 3 wercemaintained as control, therapeutic dose control (60 ppm) and toxic dose control (120 ppm) respectively. Groups 4 and 5 were fed on feed containing salinomycin @ 60 and 120 ppm, respectively, along with SA @ 125 mg/kg of feed. Groups 6 and 7 were fed on feed containing salinomycin @120 ppm for the first 5 weeks of study for induction of ionophore toxicity. For the following 2 weeks, group 6 received SA @125 mg/kg of feed and group 7 was fed on feed containing salinomyocin @ 120 ppm along with SA @ 125 mg/kg of feed. Body weights and FCR were recorded at weekly intervals revealed a significant decrease, while the activities of antioxidant enzymes (glutathione peroxidase, glutathione reductase and catalase) were significantly increased and glutathione levels decreased significantly (P&lt0.01) in toxic controls as compared to groups 1,2, 4 and 5. The biochemical parameters such as AST, total proteins, total cholesterol, triglycerides, LDL, urea, creatinine and BUN were significantly elevated in toxic controls, whereas HDL level was significantly (P&ltO.O1) lowcrcd us compared to goups 1,2,4 and 5. Following antioxidant therapy all serobiochemical parameters of groups 6 and 7 were revived to normal. Thus, it is concluded that SA is useful in feed to avoid any accidental ionophore toxicity.